Labour, state and society in rural India : a class-relational approach - Pattenden, Jonathan (Manchester Political Studies, 2016)
"Behind India's high recent growth rates lies a story of societal conflict that is scarcely talked about. Across production sites, state institutions and civil society organisations, the dominant and less well-off sections of society are engaged in a protracted conflict that determines the material conditions of one quarter of the world's 'poor'. Increasingly mobile, and often engaged in multiple occupations in multiple locations, India's 'classes of labour' are highly segmented, but far from passive in the face of ongoing processes of exploitation and domination. Drawing on detailed fieldwork in rural South India over more than a decade, the book uses a 'class-relational' approach that focuses on 'the poor's' iniquitous relations with others, and views class in terms of contested social relations rather than structural locations marked by particular characteristics. The book explores continuity and change amongst forms of accumulation, exploitation and domination in three interrelated arenas of class relations: labour relations, the state and civil society. Marginal gains for labour derived from structural change are contested by capital, local state institutions and state poverty reduction programmes tend to be controlled by the dominant class, and civil society organisations tend to reproduce rather than challenge the status quo. On the other hand, elements of state policy have the capacity to improve the material conditions of 'the poor' where such ends are actively pursued by labouring class organisations. It is argued that social policy currently provides the most fertile terrain for redistributing power and resources to the labouring class, and may clear the way for more fundamental transformations."--Publisher's description